Analisa Kualitas Website Keanggotaan Perpustakaan Menggunakan Metode Webqual 4.0 - Aprilia Warat; Eva Zuraidah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Analysis of the website Membership.perpusnas.go.id as a means of information used by members of the National Library of Indonesia. Therefore the researcher conducted an analysis of member satisfaction as users of the membership.perpusnas.go.id website service on website quality using the webqual 4.0 method which focuses on 3 dimensions of webqual 4.0 namely Usability, Information Quality and Interaction Service Quality, to measure user satisfaction (User Satisfaction). This study used a statement instrument based on the webqual 4.0 dimension, using a questionnaire distributed to 43. Data processing in this study used SPSS version 26. The results of the F test stated that there was a joint effect of the 3 dimensions of Usability, Information Quality, Interaction Service Quality on user satisfaction, with a P-Value or significance of 9.007, meaning that the Probability value was > 0.05. The results of the t test show that the Usability variable has no significant effect on user satisfaction, with a p-value of 10.658 (probability value > 0.05), the variables that have no effect are the quality of information (p-value of 9.552), and the quality of interaction services (p-value of 9.007). As for the results of the coefficient of determination test, it shows that the influence of the 3 dimensions of webqual 4.0 on user satisfaction is 76.10%, and the remaining 23.90% is influenced by other factors not used in this study.